Show that (1 - cos(2x)) / (1 + cos(2x)) = sec^2(x) - 1

First, take the side of the equation that looks most complicated because it often needs simplifying. This is the LHS in this case. The LHS has cos(2x) twice - therefore the double angle formula probably applies:cos(2x) = cos^2(x) - sin^2(x) = 2cos^2(x) - 1 = 1 - 2sin^2(x)In this case the cos(2x) = 2cos^2(x) - 1 looks most useful as we have sec^2(x) on the RHS of our equation and cos(x) = 1/sec(x).Sub the double angle formula into LHS:(1 - (2cos^2(x) - 1)) / (1 + (2cos^2(x) - 1)= (2 - 2cos^2(x)) / (2cos^2(x))= 2/2cos^2(x) - 2cos^2(x)/2cos^2(x)= sec^2(x) - 1= RHS.Therefore (1 - cos(2x)) / (1 + cos(2x)) = sec^2(x) - 1 

Answered by Louis G. Maths tutor

5657 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

integrate x^2 + ln(x)


Is a line ax+by+c=0 tangent to a circle?


Find an expression in terms of powers of cos(x) for cos(5x)


A Curve has parametric equation x=2sin(t), y= 1+cos(2t), -pi/2<=t<=pi/2. a) Find dy/dx when t=pi/3. b) Find the Cartesian equation for the curve in form y=f(x), -k<=x<=k. c) Find the range of f(x)


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences